Effect of Age on Blood Biochemical Profile in Growing Indigenous Kangayam Calves - Karumalaisamy, Devipriya; Palanisamy, Selvaraj; Santhanam, Jayachandran; Kannan, Vijay; Ganesan, Rameshkumar; Kumaravel , P (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was conducted to establish base line data about blood biochemical profile of growing indigenous Kangayam calves from 3- 12 month of age. Also, to compare the values with adult Kangayam cows. A total of 20 calves were selected under field conditions of native tracts of Sathiyamangalam, Erode and Namakkal district of Tamil Nadu and grouped into I (male calves) and II (female calves) with 10 calves in each group. The blood samples were collected from calves aged between 3 to 12 months at 3-, 6-, 9- and 12-months age to rule out all possible biochemical parameters in growing calves. To compare, blood samples were collected from male and female adult Kangayam cows (n=10). The results showed that the blood glucose and calcium in calves were significantly higher (P < 0.05) during first 3 months of age than other age groups and from adult cattle. Total cholesterol and ALT were lower (P < 0.05) in calves from 3-12 months of age than adult cattle. Whereas, total protein, albumin, globulin, triglyceride, blood urea nitrogen, creatinine, AST, ALP, GGT, phosphorus, potassium, magnesium, sodium and chloride were not differed among age groups. This will be useful to understand the changes of blood chemistry during different growing period and help to diagnose the disease conditions. More over establishing baseline values are helpful to clinicians when dealing with treatment of native breeds.